Reproduktion von „Good Morning Germany” von Mathias Kauage von 1990 (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent, 1990)
Copyright jointly or exclusively held by Iwalewahaus, CBCIU and/or Georgina Beier Estate Executor. CBCIU and Iwalewahaus identifiers currently unavailable.
Keywords: Art; Artists; Painting; Papua New Guinea; New Guinea; Iwalewahaus; Cultural Centre